2009
DOI: 10.1016/j.wear.2009.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water environment on tribological properties of DLC rubbed against brass

Abstract: The effects of the water environment, such as temperature, dissolved ions, dissolved oxygen etc., on the tribological properties of diamond-like carbon (DLC) against brass were studied as part of the development of water-lubricated hydraulics, valves and cylinders based on metals (Fe alloys, Cu alloys etc.). A ball-on-disk type tribotester was used to examine the above various factors. DLC was deposited on stainless steel disks using an unbalanced magnetron sputtering system. Pure water and quasi-tap water, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the other hand, Uchidate et al [48] found that the accumulation of alumina on brass aggravated the wear of DLC:H coatings in pure water, while the ions in tap-water slowed down the accumulation rate of alumina on brass. Therefore, the wear rate of DLC:H coatings in tap-water was lower than that of DLC:H coatings in pure water even at different temperatures (see Figure 3b).…”
Section: Aqueous Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Uchidate et al [48] found that the accumulation of alumina on brass aggravated the wear of DLC:H coatings in pure water, while the ions in tap-water slowed down the accumulation rate of alumina on brass. Therefore, the wear rate of DLC:H coatings in tap-water was lower than that of DLC:H coatings in pure water even at different temperatures (see Figure 3b).…”
Section: Aqueous Solutionmentioning
confidence: 99%
“…In addition, Uchidate et al [48][49][50] also found that the high temperature inhibited the formation of a whole lubricating film in water, which led to a high friction coefficient and wear rate. temperature inhibited the formation of a whole lubricating film in water, which led to a high friction coefficient and wear rate.…”
Section: Aqueous Solutionmentioning
confidence: 99%
“…Additionally, the high stress induced by ion bombardment during deposition and the large mechanical property mismatch between the coating and the substrate contribute to the poor adhesion demonstrated by Ashtijoo et al [27]. Furthermore, the wear and friction properties of DLC coatings under boundary lubrication conditions have been investigated by Uchidate et al [28], indicating that the wear of steel and friction is strongly affected by the hardness and surface roughness of the DLC. These factors collectively contribute to the negative impact of nitriding on the adhesion between tool steel and DLC coatings.…”
Section: Introductionmentioning
confidence: 99%
“…It has also shown that the tribo-layer is very important for the diamond-like carbon (DLC) coated surfaces 6,7) , which is the topic of great interest in the industry today. Researchers have studied tribology of the DLC rubbed against stainless steel and brass in the water and results have shown that the friction and wear are strongly affected by the tribo-layer formed on the metal counter surfaces, which varies depending on the dissolved ions and the water temperature 8,9) . It was assumed that the tribo-layer has a gel-like structure and prohibits the direct contact between the DLC and metal if it is formed properly.…”
Section: Introductionmentioning
confidence: 99%